Secondary thalamic neuroinflammation after focal cortical stroke and traumatic injury mirrors corticothalamic functional connectivity. Issue 7 (1st November 2021) - Necula, Deanna; Cho, Frances S.; He, Andrea; Paz, Jeanne T.
Abstract: While cortical injuries, such as traumatic brain injury (TBI) and neocortical stroke, acutely disrupt the neocortex, most of their consequent disabilities reflect secondary injuries that develop over time. Thalamic neuroinflammation has been proposed to be a biomarker of cortical injury and of the long‐term cognitive and neurological deficits that follow. However, the extent to which thalamic neuroinflammation depends on the type of cortical injury or its location remains unknown. Using two mouse models of focal neocortical injury that do not directly damage subcortical structures—controlled cortical impact and photothrombotic ischemic stroke—we found that chronic neuroinflammation in the thalamic region mirrors the functional connections with the injured cortex, and that sensory corticothalamic regions may be more likely to sustain long‐term damage than nonsensory circuits. Currently, heterogeneous clinical outcomes complicate treatment. Understanding how thalamic inflammation depends on the injury site can aid in predicting features of subsequent deficits and lead to more effective, customized therapies. Abstract : Focal cortical TBI or stroke in various cortical areas leads to gliosis in the functionally connected thalamocortical nuclei and of the nucleus reticularis thalami (nRT). The dotted line in the prefrontal cortex‐injured section indicates that the top and bottom halves of the brain are sourced from different bregma positions in order to display cortical injury and relevant thalamic nuclei together.